Foliar application of carbon quantum dots photosynthesis enhancer for enhancing the growth and development of green mustard (Brassica juncea) in indoor hydroponics - Chowmasundaram, Yamuna A.P.; Tan, Tong Ling; Fadzil, Nadia Izati; Nulit, Rosimah; Jusoh, Mashitah; Abdul Rashid, Suraya (Elsevier, 2025)
Advancements in sustainable agriculture are crucial for enhancing crop germination and early growth, addressing significant economic losses stemming from poor soil health, unpredictable climate conditions, and the overuse of chemical inputs that degrade ecosystems and reduce crop yields. Carbon quantum dots (CQDs), a zero-dimensional nanomaterial that functions as an artificial photosynthetic pigment, have shown significant promise in enhancing plant growth and photosynthesis. This study investigates the effects of CQDs on the growth and photosynthesis parameters (net assimilation, transpiration rate, stomatal conductance, water use efficiency and Rubisco activity) in hydroponically grown green mustard (Brassica juncea) plants. Various CQDs concentrations (0, 50, 100, 150, 200, and 400 ppm) were applied as foliar sprays. The application of CQDs foliar spray significantly enhanced the number of leaves, leaf surface area, plant height, and both fresh and dry biomass of green mustard plants. Additional parameters, including net assimilation rate, transpiration rate, stomatal conductance, and intrinsic water use efficiency (iWUE) were also examined. The results demonstrated that treatment with 150 ppm CQDs significantly increased CO2 assimilation rate and Rubisco activity by 58 % and 33 %, respectively, compared to the control. Additionally, the treatment at 150 ppm had the highest iWUE, suggesting that CQDs at this concentration efficiently uses water during photosynthesis to achieve a high yield. Furthermore, the effects of CQDs on plants under white light and red/blue (R/B) light were studied respectively. The chlorophyll fluorescence (Fv/Fm), effective quantum yield (ΦPSII), and light response curve of the control, 150 ppm, and 400 ppm treated plants were measured across different wavelengths. The electron transfer mechanisms that take place in the CQDs/chloroplast complex are described in this work. This study shows that CQDs have significant potential for increasing global agricultural production in the future.